2012
DOI: 10.1002/adsc.201100518
|View full text |Cite
|
Sign up to set email alerts
|

A Mild, Highly Efficient Addition of Alkynes to Aldehydes Catalyzed by Titanium Dioxide‐Supported Silver Nanoparticles

Abstract: Titanium dioxide-supported silver nanoparticles were utilized as a highly efficient catalyst for the addition of terminal alkynes to aldehydes to prepare propargylic alcohols with the promotion by triphenylphosphine. Both a significant support effect and a ligand effect were observed in the catalytic reaction. With this protocol, various propargylic alcohol derivatives were synthesized from aldehydes and terminal alkynes in good to excellent yields. Furthermore, the catalyst could be recovered and reused effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Although nanosilver-catalyzed A 3 -coupling of aldehydes, alkynes, and amines has been determined in 2010, the first example of 1,2addition of alkynes to aldehydes that catalyzed by silver nanoparticles was only reported in 2012. 95 In this work, Yao et al found the titanium oxide-supported silver nanoparticles could be utilized as an efficient catalyst for the direct addition of terminal alkynes to aromatic aldehydes ( More importantly, on the basis of the nanoAg@TiO 2 @PMHSIPNcatalyzed alkynylation of trifluoromethyl ketones, we developed a new concept that high-reactive substrate as a "reactive tractor" to pull transformation of low-reactive substrates, called as springboard chemistry or HDL catalysis, in which we found trifluoromethyl ketone could be used as a high-reactive additive for the activation of nanosilver-catalyzed alkynylation of aldehydes dramatically. 96 The nanosilver-catalyzed alkynylation of aromatic aldehydes proceeded in good to high yields under optimized reaction conditions (Scheme 37, up to 99% yield).…”
Section: Other Catalytic Reactions To Valuable Chemicals Catalyzed Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Although nanosilver-catalyzed A 3 -coupling of aldehydes, alkynes, and amines has been determined in 2010, the first example of 1,2addition of alkynes to aldehydes that catalyzed by silver nanoparticles was only reported in 2012. 95 In this work, Yao et al found the titanium oxide-supported silver nanoparticles could be utilized as an efficient catalyst for the direct addition of terminal alkynes to aromatic aldehydes ( More importantly, on the basis of the nanoAg@TiO 2 @PMHSIPNcatalyzed alkynylation of trifluoromethyl ketones, we developed a new concept that high-reactive substrate as a "reactive tractor" to pull transformation of low-reactive substrates, called as springboard chemistry or HDL catalysis, in which we found trifluoromethyl ketone could be used as a high-reactive additive for the activation of nanosilver-catalyzed alkynylation of aldehydes dramatically. 96 The nanosilver-catalyzed alkynylation of aromatic aldehydes proceeded in good to high yields under optimized reaction conditions (Scheme 37, up to 99% yield).…”
Section: Other Catalytic Reactions To Valuable Chemicals Catalyzed Bymentioning
confidence: 99%
“…The effect of particle size of nanosilver on catalytic addition of alkyne 86a to aromatic aldehyde 85a 95. …”
mentioning
confidence: 99%
“…Later, copper salts, In 2 O 3 NPs, Fe III , cobalt, Ag I , and AuNPs were also employed as catalysts in the AHA coupling reaction. In addition, the deprotonation of C sp −H bonds by AgNPs has been reported . However, the development of a new highly efficient and environmentally friendly AgNP catalytic system for the AHA coupling reaction is still desirable.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, the deprotonation of C sp ÀHb onds by AgNPsh as been reported. [19,47] However, the development of anew highly efficient and environmentally friendly AgNP catalytic system for the AHA coupling reactioni s still desirable.…”
Section: Catalytic Activity Of the Supported Catalysts In The Threecomentioning
confidence: 99%
“…[ 3 ] Silver chloride salt or silver nanoparticles in combination with tertiary phosphines is a well‐established method to efficiently catalyze A3 coupling reactions in water. [ 4–22 ] Progress in the synthesis of highly ordered mesoporous organic polymers has allowed their surface decoration with transitions metal ions via grafting techniques. [ 23,24 ] Transition metal ion‐grafted mesoporous organic polymers were utilized by various groups as efficient catalysts in the multicomponent coupling reactions.…”
Section: Introductionmentioning
confidence: 99%